Application of Gastroscopy in the Diagnosis of Congenital Pyriform Sinus Fistula in Children - Wang, Shengcai; Mei, Lin; Li, Yanzhen; Zhang, Xuexi; Zhang, Jie; Ge, Wentong; Guo, Yongli; Yu, Yongbo; Wang, Guoli; Mei, Tianlu; Liu, Qiaoyin; Sun, Nian; et al. (Frontiers in Pediatrics, 2021)
Objective: The aim of this study was to explore the diagnostic value of gastroscopy under local anesthesia for congenital pyriform sinus fistula (CPSF). Methods: This research was a diagnostic study. Patients received gastroscopy under local anesthesia to diagnose CPSF, and suspension laryngoscopy under general anesthesia was performed 2 days after gastroscopy. Various conditions of the internal opening of CPSF were then recorded. Patients were grouped according to lesion sides, age, time after the inflammation subsided, and history of previous surgery. The sensitivity, specificity, area under the receiver operating characteristic curve (AUC), accuracy, and positive and negative predictive values of gastroscopy were compared between the groups. Results: A total of 48 patients were recruited in this study, and no patients had severe gastroscopy-related complications. The diagnostic values of gastroscopy in 41 cases (85.4%) were consistent with suspension laryngoscopy. The sensitivity of gastroscopy was 86.4%, the specificity was 75%, the AUC was 0.807, the positive prediction rate was 97.4%, the negative prediction rate was 33.3%, the accuracy rate was 85.4%, and the diagnostic odds ratio (DOR) was 2.1. The kappa consistency test results had statistical significance (P = 0.0026, kappa = 0.3913). The diagnostic value of gastroscopy was better for the patients with inflammation subsiding for more than 4 weeks (P < 0.0001). Conclusion: Gastroscopy under local anesthesia is a safe, effective, reliable and novel diagnostic method for CPSF, and it is especially recommended as a diagnostic method for the patients with inflammation subsiding for more than 4 weeks.